The Effect of Health Education Using Animated Videos on Attitudes Regarding the Importance of Breakfast Among 4th and 5th Grade Elementary School Students - Oktavianto, Eka; Nurhalisah, Nurhalisah; Timiyatun, Endar (ProNers, 2025)
Background: Breakfast plays an important role in fulfilling balanced nutrition, especially for school-age children. However, many students are not accustomed to eating breakfast, resulting in risks of decreased concentration, reduced immunity, and digestive disorders. Educational media such as animated videos have the potential to improve students' understanding and attitudes toward the importance of breakfast. Objective: To determine the effect of health education using animated videos on students' attitudes about the importance of breakfast. Methods: This study used a pre-experimental design with a one-group pre-test post-test approach. The sample consisted of 36 students from grades 4 and 5 selected through accidental sampling. The intervention consisted of an animated video lasting 4 minutes and 13 seconds. Data collection used attitude questionnaires, and analysis was performed using the Wilcoxon test. Results: Students' average attitude scores increased from 7.03 before the intervention to 9.69 after, with a difference of 2.66 points. The Wilcoxon test showed a p-value = 0.000 (p < 0.05), indicating a significant effect of the intervention on students' attitudes. Conclusion: Health education through animated videos is effective in improving students' attitudes toward the importance of breakfast and can serve as an alternative nutrition education medium at the elementary school level.